2017
DOI: 10.2134/agronj2016.09.0495
|View full text |Cite
|
Sign up to set email alerts
|

Field‐Scale Evaluation of Biosolids‐Derived Organomineral Fertilizers Applied to Winter Wheat in England

Abstract: Field-scale experiments in four crop seasons established the agronomic performance of biosolids-derived organomineral fertilizers (OMF) for winter wheat (Triticum aestivum L.) production in England. Two OMF formulations (OMF 10 10:4:4 and OMF 15 15:4:4) were compared with urea and biosolids granules (≈5:6:0.2) to determine crop responses and fertilizer eff ects on soil chemical properties. Fertilizers were applied at N rates between 0 and 250 kg ha -1 at regular increments of 50 kg ha -1 N. Average grain yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 91 publications
2
12
0
1
Order By: Relevance
“…Previous research suggested that bahiagrass herbage accumulation has been shown to be restricted under shorter‐photoperiod winter months in Florida (Mislevy & Everett, 1981). Similarly, the cooler temperatures were also not conducive to mineralization of organic N present in biosolids, which could potentially affect N availability for the crop and subsequent yield potential (Antille et al., 2017; Wang et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggested that bahiagrass herbage accumulation has been shown to be restricted under shorter‐photoperiod winter months in Florida (Mislevy & Everett, 1981). Similarly, the cooler temperatures were also not conducive to mineralization of organic N present in biosolids, which could potentially affect N availability for the crop and subsequent yield potential (Antille et al., 2017; Wang et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A significant body of literature has demonstrated numerous agronomic benefits associated with land application of biosolids to pastures (Adjei & Rechcigl, 2002; Barbarick, Doxtader, Redente, & Brobst, 2004; Sigua et al., 2005). Land application of biosolids to perennial pasture provides essential plant nutrients and organic matter and serve as a liming agent to acid pasture soils (Adjei & Rechcigl, 2002; Antille et al., 2017; Avery et al., 2018; Liu, Fike, Galbraith, & Fike, 2015a, 2015b; Sigua et al., 2005; Tiffany et al., 2001a, 2001b). Research demonstrated that when applied at equivalent N rates, biosolids resulted in either similar or greater forage production as inorganic fertilizer (Adjei & Rechcigl, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, crop yield is the generic function of N supply from both soil and the applied fertilizer source. Under suboptimal N fertility conditions, combining both chemical and organic fertilization may ensure slow but steady release of nutrients to ensure higher farm productivity in semiarid agriculture, and this is especially the case for N. Such crop responses also suggest that the occurrence of N‐related stress before anthesis is reduced by the slow release nature of applied fertilizer, leading to improvements in grain yield (Antille et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Yield-to-nitrogen response relationships were examined by applying nonlinear regression analyses, and by fitting quadratic functions to the data (Abraham and Rao, 1966). The approach used in this work is from studies (e.g., Kachanoski, 2009;Antille et al, 2017) dealing with cereal crop responses to applied N fertilizer, and assumes a quadratic-plateau relationship. Crop's gross margin (GM) was estimated as the difference between gross income (GI) and total variable costs (TVC) (Galambošová et al, 2017).…”
Section: Crop Measurements and Analysesmentioning
confidence: 99%